TESTING THE QUALITY OF THE ORTHOFOTO DMC III LARGE FORMAT CAMERA AERIAL PHOTOGRAPHY FOR BASE MAP ACCURACY SCALE 1:5000 - Muhammad Farhan; Wikan Jaya Prihantarto (Remote Sensing Technology Study Program, 2025)
This study discusses the quality testing of the DMC III LFAP camera for base map accuracy at a scale of 1:5000. The objectives of this research are to analyze the resolution quality of DMC III LFAP orthophoto images and to assess the geometric accuracy of DMC III LFAP orthomosaics based on Independent Check Points (ICP) measured in the field.This research employs both qualitative and quantitative methods. The study focuses on two main aspects: the resolution quality of orthophoto images and geometric accuracy based on ICP measurements. The research data includes DMC III aerial photographs from 2021 and field ICP observations. The methods used in this study involve orthophoto processing, ICP measurements using Geodetic GPS, and geometric accuracy analysis with the Root Mean Square Error (RMSE) method. Accuracy evaluation is conducted by comparing orthophoto coordinates with field observations.The results indicate that the resolution of the generated orthophoto images meets the quality standards for a scale of 1:5000 based on Per BIG Number 1 of 2020, with a reliable level of accuracy. However, geometric accuracy testing shows that the orthomosaic results have an error level exceeding the tolerance limits set by Per BIG Number 6 of 2018, making them unsuitable for base map accuracy at a scale of 1:5000.